Business mathematics - Aufmann, Richard N.; Barker, Vernon C.; Lockwood, Joanne S. (Boston MA : Houghton Mifflin, 1994)
This book is about: Whole numbers and business applications; Fractions and business applications; Decimals and business applications; Equations; Percent and business applications;...
Keywords: Business mathematics; Business mathematics